Differential diagnosis between normal non-fluency & stuttering - Sowmya Srinivasan (Journal of All India Institute of Speech and Hearing, 1970)
What differentiates stuttering from normal non-fluency is a question which still draws debates. Several authors (Davis, 1939; Johnson, 1982; Egland,1955; Meyers, 1989) have tried to list the features which delineate stuttering form normal non-fluency but of no avail. Till now, no consensus has beenreached among the Speech Pathologists as to what features constitute stuttering and what constitute normal non-fluency.